Influences of crystal anisotropy in pharmaceutical process development - Hadjittofis,E; Isbell,M; Karde,V; Varghese,S; Ghoroi,C; Heng,JYY (Pharmaceutical Research, 2018)
Crystalline materials are of crucial importance to the pharmaceutical industry, as a large number of APIs are formulated in crystalline form, occasionally in the presence of crystalline excipients. Owing to their multifaceted character, crystals were found to have strongly anisotropic properties. In fact anisotropic properties were found to be quite important for a number of processes including milling, granulation and tabletting. However, an understanding of crystal anisotropy and an ability to control and predict crystal anisotropy are mostly subjects of interest for researchers, as they can have a profound influence on the development of more efficient process development approaches. A number of studies dealing with the aforementioned phenomena are grounded on over-simplistic assumptions, neglecting key attributes of crystalline materials, most importantly the anisotropic nature of a number of their properties. Moreover, concepts such as the influence of interfacial phenomena in the behaviour of crystalline materials during their growth and in vivo, are still poorly understood. The review aims to address concepts from a molecular perspective, focusing on crystal growth and dissolution. It begins with a brief outline of fundamental concepts of intermolecular and interfacial phenomena. The second part discusses their relevance to the field of pharmaceutical crystal growth and dissolution. Particular emphasis is given to works dealing with mechanistic understandings of the influence of solvents and additives on crystal habit. Furthermore, comments and perspectives, highlighting future directions for the implementation of fundamental concepts of interfacial phenomena for the rational understanding of crystal growth and dissolution processes, have been provided.